Vibration diagnosis of a gearbox by wavelet bicoherence technology - Gelman, Leonid; Solinski, Krzysztof; Shaw, Brian A.; Vaidhianathasamy, Moorthy (British Institute of Non-destructive Testing, 2017)
Gearboxes are critical elements of mechanical systems that are widely used in aerospace, energy generation, land and naval applications. The early detection of changes in the technical condition of this equipment is of great importance for the optimisation of maintenance costs. Vibration signal components resulting from the presence of the developing faults of meshing gears contain the information that, once extracted from the signal, may allow for a reliable estimation of the technical condition of the meshing gears. Wavelet bicoherence (WB)-based technology has been used to obtain the signal feature characterising the phase relationship between the signal components generated by gear faults in the selected frequency bandwidths. In previous research, WB has been successfully applied to the detection of artificially-created gearbox faults. This paper will present the application of WB in the detection of naturally-developing gear faults.